Gambaran Kegiatan Kerja PMIK pada Pelaksanaan Pelepasan Informasi Medis kepada Pihak Asurasi di RSUD Tarakan Jakarta - Rani Yulistianingsih; Muhammad Fuad Iqbal; Dina Sonia; Noor Yulia (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
The release of medical information is the process of disclosing or sharing information about a patient's health condition, medical history, or medical examination results with other parties. Due to the sensitive nature of the information contained in medical records, healthcare providers are obligated to ensure that all information is appropriately accountable. This study aims to explore the work activities of medical record officers and health information management in the process of releasing medical information to insurance parties at Tarakan Regional General Hospital (RSUD Tarakan). This research uses a descriptive method with a qualitative approach by explaining the results of interviews regarding the work activities of medical record officers and health information management in the process of releasing medical information to insurance parties. RSUD Tarakan already has standard operating procedures related to the release of medical information, both to insurance parties that cooperate and to those that do not cooperate. In the work activities of the officers, the stages of data collection for insurance types, the request flow stage, data collection stage, data processing stage, and data presentation stage involve the insurance services and fundraising departments in the release process for cooperating insurance parties. Meanwhile, the medical records department and the information department are only involved in the release of medical information to non-cooperating insurance parties. The challenges in releasing medical information to non-cooperating insurance parties include the lack of requirements provided by patients, as they are often unaware of the necessary documents and the process for requesting the release of medical information, which can cause delays in the process.